Pengaruh DER, PER dan ROA Terhadap PBV Pada Industri Perbankan - Firdaus, Iwan (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2019)
This research is to find out the influence of DER, PER and ROA to PBV in the banking industry published on Indonesia Stock Exchange for the period 2013-2017. Sample selection with purposive sampling method as many as 21 companies, totaling 105 data. The method used in this research is panel data regression analysis and it is found that the more appropriate model used is fixed effect. From result of research got value of adjusted R-Square equal to 15.86%. Partially show that DER, PER variable have positive and significant effect on PBV. ROA variable partially have positive and no significant effect to PBV.